2018
DOI: 10.1080/00275514.2018.1515449
|View full text |Cite
|
Sign up to set email alerts
|

New species ofCortinariussect.Austroamericani, sect. nov., from South American Nothofagaceae forests

Abstract: In this study, we document and describe the new Cortinarius section Austroamericani. Our results reveal high species diversity within this clade, with a total of 12 recognized species. Of these, only C. rufus was previously documented. Seven species are described as new based on basidiomata collections. The four remaining species are only known from environmental sequences. All examined species form ectomycorrhizal associations with species of Nothofagaceae and are currently only known from Argentinean and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This approach and level of grouping mainly corresponds to the concepts previously used to delimit the sections in the genus Cortinarius in the era of molecular data (e.g. Ammirati et al 2013Ammirati et al , 2017Dima et al 2014;Liimatainen et al 2015Liimatainen et al , 2017Liimatainen et al , 2020Niskanen et al 2009Niskanen et al , 2011Niskanen et al , 2013San Fabian et al 2018;Soop et al 2019).…”
Section: Sectionsmentioning
confidence: 99%
“…This approach and level of grouping mainly corresponds to the concepts previously used to delimit the sections in the genus Cortinarius in the era of molecular data (e.g. Ammirati et al 2013Ammirati et al , 2017Dima et al 2014;Liimatainen et al 2015Liimatainen et al , 2017Liimatainen et al , 2020Niskanen et al 2009Niskanen et al , 2011Niskanen et al , 2013San Fabian et al 2018;Soop et al 2019).…”
Section: Sectionsmentioning
confidence: 99%
“…However, aside from the pioneering work from Moser and Horak [ 5 , 26 ] there are relatively few studies that have focused on South American Cortinarius diversity [ 25 ]. Recent studies describing several new species or even new sections highlight this knowledge gap [ 8 , 12 , 15 , 16 , 67 ]. Based on our current knowledge, the Cortinarius species associated with Nothofagaceae species rarely or never occur outside the distribution range of their host trees [ 26 , 71 , 72 , 73 , 74 , 75 ], making it highly likely that, after losing the connection via Antarctica, endemic Cortinarius lineages evolved in South America and Australasia.…”
Section: Discussionmentioning
confidence: 99%
“…Even though several authors have contributed to the knowledge of Cortinarius associated with South American Nothofagaceae forests ([ 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], among others), the biodiversity of this genus in the Southern Hemisphere is incredibly high and remains insufficiently studied [ 23 , 24 ]. Recent studies showed, for example, that C. magellanicus , which was previously reported as widely distributed and shared among various Nothofagaceae hosts in the Southern Hemisphere [ 5 , 6 , 25 , 26 , 27 , 28 , 29 ], is a complex of species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bougher and Hilton 1989;Soop 2005;Gasparini and Soop 2008), South America (e.g. Valenzuela and Esteve-Raventos 1994;Garnica et al 2003;San-Fabian et al 2018) and Asia (e.g. Miyauchi 2001;Peintner et al 2003;Xie et al 2019).…”
Section: Introductionmentioning
confidence: 99%